Sachiko Murata: Islam, Gender and Islamic Education - Maoshul, Derry Ridwan; Sumadi, Sumadi (TAJDID, 2023)
Feminists advocate for gender equality, aiming to ensure that women are granted the same rights as men. They evaluate the subjugation endured by women due to a patriarchal societal structure that privileges men and marginalizes women. Feminists not only rectified the social system, but also rectified religion due to its perceived gender discrimination in their teachings. The concept of equality of rights refers to the notion of identical rights. This concept has also extended to the realm of education and is deemed to engender novel societal issues due to its origins in power dynamics. This article will elucidate the notion of gender as a foundation for education, drawing from Sachiko Murata’s perspectives. This suggests the inference that education should adopt an equitable paradigm in perceiving women and men as individuals. Women and men are distinct genders, each characterized by their own unique biological and physiological attributes. Nevertheless, both entities have an equivalent function in existence, hence it is imperative to establish a celestial connection.